Efficacy of DOTS therapy in Pulmonary Tuberculosis with Diabetes Mellitus - Nigam, Pradeep; Baghel, P K.; Jain, M.K.; Kandambe, Sagar (International Journal of Medical Research and Review, 2014)
Diabetic persons are more susceptible to develop tuberculosis than non diabetics. What makes the diagnosis of combination difficult, is the fact that symptoms of complicating disease being masked by coexisting disease. Poor glycemic control helps in proliferation of tuberculosis and tuberculosis itself leads to poor glucose control. Thus both deteriorate each other. Directly Observed Treatment Short course has been found to be equally effective in patients with and without diabetes with pulmonary tuberculosis. Method: The patients of either sex with pulmonary tuberculosis and associated diabetes mellitus admitted in medical ward excluding chronic cases. Pulmonary tuberculosis was diagnosed by examination of sputum for AFB and by clinical and radiological assessment. Diabetes mellitus was diagnosed from history, previous records and blood examination as per ADA criteria. Results: The cure rate was 82% in diabetic group and 86% in non-diabetic group with failure rate of 6% and 4% in diabetic group and non diabetic group respectively. Conclusion : Patients with pulmonary tuberculosis having age more than 40yrs and lower lobe lesions should be subjected to O.G.T. to rule out occult diabetes.